2018
DOI: 10.1136/bmjebm-2018-111019
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based practice education for healthcare professions: an expert view

Abstract: Internationally, evidence-based practice (EBP) is recognised as a foundational element of healthcare professional education. Achieving competency in this area is a complex undertaking that is reflected in disparities between ‘best EBP’ and actual clinical care. The effective development and implementation of professional education to facilitate EBP remains a major and immediate challenge. To ascertain nuanced perspectives on the provision of EBP education internationally, interviews were conducted with five EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
175
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(185 citation statements)
references
References 32 publications
(40 reference statements)
5
175
1
4
Order By: Relevance
“…Encouraging students to learn together by allowing them to complete the formative assessment (EP) together during clinical practice and peer mentoring at the annual conference where students show their peers how they applied EBM in clinical practice may have had a positive effect in our study. This supports previous studies which have demonstrated the bene ts of scaffolding student learning or spiral approach to EBM teaching; where EBM concepts and applications increase in complexity and are reinforced throughout the curriculum (19)(20)(21). Our teaching model provides a great example of continually shifting the zone of proximal development (Leppink & Duvivier 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Encouraging students to learn together by allowing them to complete the formative assessment (EP) together during clinical practice and peer mentoring at the annual conference where students show their peers how they applied EBM in clinical practice may have had a positive effect in our study. This supports previous studies which have demonstrated the bene ts of scaffolding student learning or spiral approach to EBM teaching; where EBM concepts and applications increase in complexity and are reinforced throughout the curriculum (19)(20)(21). Our teaching model provides a great example of continually shifting the zone of proximal development (Leppink & Duvivier 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, students are learning in a context of altered priorities -what matters during this pandemic -and this is likely to influence the way they care for women, babies, and families on into the future ( Lehane et al , 2019 ).…”
Section: Decision-making In Times Of Uncertaintymentioning
confidence: 99%
“…Supporting clinical instructors to be con dent in terms of their own competence when teaching EBP and to present themselves as role models for students, can assist students in applying EBP during clinical placements (1).…”
Section: Resultsmentioning
confidence: 99%
“…On an international scale, evidence-based practice is expected to be included in occupational therapy education (1). Evidence-based occupational therapy is de ned as "the client-centred enablement of occupation, based on client information and a critical review of relevant research, expert consensus and experience" (2).…”
Section: Introductionmentioning
confidence: 99%